2014
DOI: 10.1002/dta.1756
|View full text |Cite
|
Sign up to set email alerts
|

Study on the phase I metabolism of novel synthetic cannabinoids, APICA and its fluorinated analogue

Abstract: The data are reported for an in vitro metabolism study of two novel synthetic cannabinoids, N-(1-adamantyl)-1-pentyl-1H-indole-3-carboxamide (APICA) and its fluorinated analog N-(1-adamantyl)-1-(5-fluoropentyl)-1H-indole-3-carboxamide (5F-APICA, STS-135), which are active ingredients of smoking mixtures sold in Russia since 2012. The cannabinoids were isolated from herbal mixtures using preparative liquid chromatography and then incubated with human liver microsomes (HLMs). The formed metabolites were characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 41 publications
2
30
0
Order By: Relevance
“…Sobolevsky et al recently reported on analysis of forensic urine samples positive for APICA (SDB-001) and 5F-APICA (STS-135), two synthetic cannabinoids differing from AKB-48 and 5F-AKB-48, respectively, by having an indole instead of an indazole ring (Fig. 1c), and the authors also identified hydroxylations on the adamantyl ring as major biotransformations (19). When assessed, recombinant CYP3A4 metabolized these three compounds in vitro and, similarly to AKB-48, preferentially carried out hydroxylations on the adamantyl moiety (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sobolevsky et al recently reported on analysis of forensic urine samples positive for APICA (SDB-001) and 5F-APICA (STS-135), two synthetic cannabinoids differing from AKB-48 and 5F-AKB-48, respectively, by having an indole instead of an indazole ring (Fig. 1c), and the authors also identified hydroxylations on the adamantyl ring as major biotransformations (19). When assessed, recombinant CYP3A4 metabolized these three compounds in vitro and, similarly to AKB-48, preferentially carried out hydroxylations on the adamantyl moiety (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…1d). Metabolites of AKB-48 (17), 5F-AKB-48 (18), APICA (19), 5F-APICA (19,20), and AB-001 (21) have been reported, but so far not the enzymes responsible for their generation.…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge of metabolites is important for forensic and clinical cases to prove the consumption of particular cannabinoids in urinalysis because synthetic cannabinoids are generally extensively metabolised and are usually not found without modification or found in low abundance in urine, requiring abundant and specific metabolites to be targeted instead [5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…While providing the most reliable data [15], self-administration of drugs is difficult due to possible side effects and ethical concerns and therefore other approaches are commonly taken such as in vitro human hepatocytes [7][8][9][16][17][18][19][20] and human liver microsomes (HLM) [6,14,[21][22][23][24][25][26], and in vivo animals [5,[25][26][27]. The combination of controlled experiments such as human hepatocytes and authentic human urine analysis particularly appears to be valuable [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies have been performed in order to elucidate the main metabolic pathways of some NPS by using several approaches, such as drug incubation with human liver microsomes (HLM) [17][18][19][20][21] or with human hepatocytes, [22][23][24] as well as controlled-drug administration to rats. [25,26] Furthermore, these studies are now advantageously supported by the use of powerful software which helps in the elucidation of the metabolite chemical structures.…”
Section: Introductionmentioning
confidence: 99%